(untitled) (Asian-Australasian Journal of Food Safety and Security, 2018)
A survey study was conducted to estimate the cost, returns, relative profitability and practices of Pineapple mono-crop and Pineapple inter-crops production in Madhupur area of Tangail District. Data was collected personally through prepared interview schedule from 60 randomly selected Pineapple growers from Ausnara, Oronkhola, Sonia and Motel bazar union under Madhupur Upazila of Tangail District during July to October 2013. A simple random sampling was followed to select the farmers in the study area. Both tabular and statistical analyses were applied in this study. Cost and return analysis showed that total cost incurred for producing Pineapple mono crop, Pineapple+Papaya and Pineapple+Banana+Aroid were Tk.312849.72, Tk.395894.01 and Tk.377013.25 per hectare respectively. Per hectare net return for Pineapple + Papaya and Pineapple + Banana + Aroid production were Tk.492111.00 and Tk.195704.75 which were higher than that of Pineapple mono crop (Tk.157675.28). On the other hand BCR for Pineapple + Papaya and Pineapple + Banana + Aroid production were 2.24 and 1.52 which were higher than that of Pineapple mono crop (1.50). It represents that both pineapple mono-crop and pineapple inter-crops production are profitable among them Pineapple-inter crops cropping pattern is more profitable then Pineapple-mono crop. About 80% of pineapple growers grow papaya, banana, zinger, turmeric and aroids as intercrops with pineapple. The study identified some crucial problems and probable solutions suggested by the farmer. Finally, some policy recommendations were suggested and avenues for further research were shown. Asian Australas. J. Food Saf. Secur. 2018, 2(2), 56-64